Development of membrane oxygen enrichment system for wastewater aeration system - Chan, Fook Kiong; Ismail, Ahmad Fauzi; M. Yusof, M. Rashid (2000)
The availability of hollow fiber membranes and membrane modules has brought forth the development of simple processes for the production of oxygen and nitrogen from ambient air. In conventional wastewater aeration systems, compressed air is directly injected into the wastewater for aeration processes. However, air contains only 21 percent of oxygen and most of this oxygen is often not ideally transfer into liquid phase, thus making it difficult to obtain even the minimal dissolved oxygen level required to sustain organism growth and maintain the desired production level. The simplicity and low capital investment of membrane oxygen enrichment system have lead to the development of membrane system for oxygen enrichment. The aim of this particular project is to apply the locally produced asymmetric polysulfone hollow fiber membranes into a locally developed air separation system, which able to enrich the percentage of oxygen into wastewater aeration system for oxidation processes. This would reduce time required for oxidation and simultaneously reduces energy consumption in the compressor thus leading to an ultimate cost saving.